Understanding the Environmental Factors Promoting Student Creativity in Appropriate Design of Learning Spaces - Rashidi, Seyed Mansour (International Journal of Psychosocial Rehabilitation, 2020)
The environment is one of the first places to be influencial on human behavior and mind, which can promote the growth of body and soul and can induce various behaviors in human society. On the other hand, the architectural environment plays an important role in enhancing the quality of education and creativity in human interaction with other influenced elements such as physical elements, objects, individuals, material factors, and a sense of belonging. People spend about one-third of their childhood, adolescence, and youth in educational settings. Nowadays, in the design of learning spaces, more attention has been paid to quantitative needs and many qualitative concepts have been abandoned, although it is the qualitative concepts that make users more motivated and feel belonging to the place. In this regard, understanding the environmental elements of learning spaces, making them flexible based on student interactions, maximizing environmental capabilities, and the potential for evolutionary flexibility and growth over time, will have a major role in enhancing the quality of education. The purpose of the present study is to provide optimal design methods for indoor and outdoor spaces , green spaces, improvement of environmental factors, play environment, attention to environmental psychology and physical and psychological needs of children and create a learning space that is in harmony with the needs of the learner, which can promote creativity, motivation and are prone to improve children’s learning and behavior. Finally, it can be concluded that the principles of environmental psychology interact with architectural principles to create an effective model for the design of creative learning spaces, and the available studies are intended to validate this hypothesis and provide appropriate design strategies. The research method of this article is descriptive and based on authentic and new scientific library studies, documents and scientific findings.